Sustainable tourism village development strategy to improve community welfare through a balanced scorecard approach in jombang regency - Mas’adah Mas’adah; Mokhtar Sayyid; Dadang Wiratama; Nano Firmasyah; Sharita Aulia Rochmi (Institute of Computer Science (IOCS), 2026)
The purpose of this study is to analyze and formulate an effective sustainable tourism village development strategy to improve the welfare of the community in Jombang Regency, especially through the Balanced Scorecard approach. The method in this study uses a qualitative case study approach. This study focuses on finding facts about a social phenomenon. Data analysis uses Miles Huberman's qualitative analysis consisting of data reduction, data presentation, and conclusions. The results of the study include four sustainable tourism village development strategies using the Balanced Scorecard approach, namely: 1. The Financial Perspective shows that the contribution of Pandansili tourism to PADes has begun to be seen with an increase in income of around 25%, but there is still a need for diversification of income sources. 2. The Customer Perspective confirms that visitor satisfaction is quite good (78%), but there is still a need for improvement in tourism services. 3. The Internal Business Process Perspective reveals that although BUMDes Maju Sejahtera has had a management SOP, its implementation is not optimal. Service digitalization is needed. 4. The Learning and Growth Perspective highlights the limited competency of local human resources in digital management and marketing. Development strategies should focus on training, empowering the younger generation, and innovating tourism products. In conclusion, overall, the application of the Balanced Scorecard approach provides a comprehensive strategic framework in describing the direction of sustainable development of Pandansili Tourism Village, by balancing financial aspects, visitor satisfaction, internal processes, and human resource development